Personal Hygiene Pekerja Dalam Proses Produksi Nugget Ikan Lele Dumbo (Clarias Gariepinus) Di Pusat Pelatihan Mandiri Kelautan Dan Perikanan (P2MKP) Karya Lestari Bali - Ray Nasrullah Nasrullah; Eka Saputra (Universitas Airlangga, 2019)
Nugget is one type of ready-to-eat frozen product. Nugget is made from ground meat which is given spices, a binder mixture, then cured, steamed, cut and covered with flour adhesive (dough) and covered with bread flour (breading). Field Work Practice is to study and learn the personal hygiene of workers in the process of producing nuggets of dumbo catfish (Clarias gariepenus) at P2MKP Karya Lestari Tabanan, Bali. This Praktek Kerja Lapang Activity uses descriptive observative method which is a method in solving a problem by describing and explaining the situation and condition of an object of observation based on direct observations and facts that occur in the field. Data collection in this Praktek Kerja Lapang activity uses primary data collection methods from interviews, active participation and observations, and secondary data through literature study. The application of personal hygiene in P2MKP has been carried out well in accordance with standards including the use of closed clothing, using gloves according to standards, maintaining the health and safety of workers and prohibiting the use of personal equipment made of metal. But the knowledge of personal hygiene workers is not evenly distributed because some workers have not received training facilities on personal hygiene as a whole, it is an obstacle in the application of personal hygiene workers.